"Hammered down on every side" versus "just being positive": A critical discursive approach to health inequality. (22nd May 2017) - Anderson, Emma; Gibson, Stephen
Abstract: Socio‐economic and health inequality are strongly linked and are increasingly perpetuated by discourses of individual responsibility. However, little research from a critical discursive perspective has addressed how people affected themselves may account for this relationship. This research examined the ways in which people who are in debt, unemployed, or in insecure, minimum‐wage employment construct health and negotiate identities around it. Data from semistructured interviews with 6 participants were analysed and 3 main interpretative repertoires were identified: a medical repertoire of health as a lack of illness; health as adopting the "right" behaviours and attitudes; and health as being heavily influenced by external factors, such as income and life circumstances. The analysis focuses on how participants managed the tension between these latter 2 repertoires by adopting various subject positions around health: that it is "slipping" away from them; that it requires motivation; and that it is unattainable. Underpinning this is a "common‐sense" idea of health as something that is worked towards through culturally approved actions and attitudes.